Understorey fire propagation and tree mortality on adjacent areas to an Amazonian deforestation fire - Carvalho, J. A.; Gurgel Veras, C. A.; Alvarado, E. C.; Sandberg, D. V.; Leite, S. J.; Gielow, R.; Rabelo, E. R. C. [UNESP]; Santos, J. C. (CSIRO Publishing, 2010)
Fire characteristics in tropical ecosystems are poorly documented quantitatively in the literature. This paper describes an understorey fire propagating across the edges of a biomass burn of a cleared primary forest. The experiment was carried out in 2001 in the Amazon forest near Alta Floresta, state of Mato Grosso, Brazil, as part of biomass burning experiments conducted in the same area since 1997. The vegetation of a 200 x 200-m(2) forested area was clear-cut in early June and burned in late August. The understorey fire that escaped from the main burn was monitored across the four sides of the land clearing area. Flame-front spread varied between 0.14 and 0.35 m min(-1). Maximum flame height was about 30 cm and typical flame depth was 10 to 15 cm. Tree mortality was investigated in 2003 in four areas adjacent to the biomass burning experiment. A total of 210 trees were counted in the four areas, 29.5% were dead as a consequence of the understorey fire that had occurred 2 years before. This fire-caused mortality is evidence of the synergistic effect between slash burning, tree mortality and future fire vulnerability on the forest-land clearing interfaces.
Keywords: biomass combustion; escaped fires; tropical forest